PENGARUH BRAND AMBASSADOR, BRAND IMAGE, DAN KUALITAS PRODUK TERHADAP MINAT BELI PRODUK SKINCARE SKINTIFIC - Oktavia, Silvia Selsa; Istiono, Istiono (Cahaya Ilmu Bangsa, 2024)
ABSTRACT Based on data from the Compas Dashboard (2023) regarding local and imported skincare sales, it shows that of the five top brands in that period, three of them implemented a branding strategy involving Korean artists, while Skintific, as an imported brand, did not implement the same strategy. This strategy has proven effective for other brands such as Whitelab, which managed to record its best performance in the period 1-15 September. This phenomenon indicates that competition does not only occur between local skincare brands, but also between imported brands in the market. Therefore, several brands have begun to optimize special strategies to increase consumer buying interest in Skintific skincare products. This research aims to test and analyze the influence of Brand Ambassador, Brand Image and Product Quality on Purchase Interest in Skintific Skincare Products, both partially and simultaneously. This research was conducted on students of the Management Study Program, Faculty of Economics and Business, University of 17 August 1945 Surabaya. This research was conducted on a sample size of 100 respondents who were collected using a questionnaire and the data tests used were instrument tests, classical assumption tests, t tests and F tests. Data analysis used multiple linear regression coefficient of determination (R2) with SPSS 27. The results of this research are that Brand Ambassador, Brand Image and Product Quality simultaneously have a significant effect on Interest in Buying Skincare Products, Brand Ambassador has a positive and significant effect on Interest in Buying Skincare Products, Brand Image has a positive effect on Interest in Buying Skincare Products, Quality Products have a significant positive effect on Purchase Interest in Skintific Skincare Products. Keywords: Brand Ambassador, Brand Image and Product Quality, Purchase Interest.